Mid-Career Award by the Association of Information Systems - Polyviou, Ariana (My University, 2026)
About the AIS Mid-Career Award The AIS Mid-Career Award recognizes individuals in the middle stages of their careers who have already made outstanding research, teaching, and/or service contributions to the field of information systems. A maximum of six (6) AIS Mid-Career Awards will be granted each year, with at least one (1) per AIS region. It is possible to be less/none if the Committee decides. Qualifications for the Award At the time of nomination be between seven (7) years and twenty (20) cumulative years after their doctoral degrees OR be within the first twenty (20) cumulative years of their academic career if they do not have a doctoral degree; Have made significant contributions to the discipline in terms of advancing and/or disseminating knowledge, engaging IS pedagogy, and service to the wider community; Garner recognition from professionals, academics and entities outside of the IS discipline; Be esteemed for their high levels of professional and personal integrity; Have not received the AIS Mid-Career Award previously; and Normally not have achieved the highest academic rank within their national/regional context. Candidates must be current members of the AIS at the nomination and receipt of recognition and (1) have been an AIS member for at least two (2) consecutive years immediately prior to the nomination or (2) have been an AIS member for five (5) cumulative years of their academic career.
Keywords: Worlds Top Scientists